EVALUATION OF FLEXURAL STRENGTH OF SINGLE-SHADE COMPOSITE RESINS WITH NANOFILLED COMPOSITE RESINS - Mozartha, Martha; Erinna Rizky Fade; Bebbi Arisya Kesumaputri; Danica Anastasia (Majalah Kedokteran Sriwijaya, 2023)
Background:The use of nanofiller in the composite resin improves the mechanical and aesthetic properties and is suitable for anterior and posterior teeth. However, the color-matching procedure is time-consuming and requires professional skills. A single-shade composite resin was developed and claimed to match all tooth colors.Objective: To evaluate the flexural strength of single-shade composite resin compared to conventional nanofilled composite resin.Method:This experimental study used specimens measuring 25 x 2 x 2 mm, divided into two groups (n = 10): single-shade composite resin and nanofilled composite resin. Flexural strength was tested using the Universal Testing Machine. The independent t-test was used to analyze the data statistically.Result: The mean value of the flexural strength of single-shade nanofilled composite resin was 110.40 MPa and 106.88 MPa, respectively. Independent t-test results (p > 0.05) showed no significant differences between groups.Conclusion: There was no significant difference in flexural strength between single shade composite resin and conventional nanofilled composite resin.